1988
DOI: 10.1136/bmj.297.6651.757
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of employees of the Atomic Weapons Establishment, 1951-82.

Abstract: A total of 22 552 workers employed by the Atomic Weapons Establishment between 1951 and 1982 were followed up for an average of 18*6 years. Of the 3115 who died, 865 (28%) died of cancer. Mortality was 23% lower than the national average for all causes ofdeath and 18% lower for cancer. These low rates were consistent with the findings in other workforces in the nuclear industry and reflect, at least in part, the selection of healthy people to work in the industry and the disproportionate recruitment of people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
4
10

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 19 publications
5
65
4
10
Order By: Relevance
“…This finding is consistent with radiation being a cause of these cancers, but does not account for most of the excess being among those not monitored for radiation exposure. An excess of these cancers has not been found in other studies of nuclear workers and nor has an association with radiation dose (Beral et al, 1988;Fraser et al, 1993), and our findings are difficult to interpret. For 35 of the 53 deaths from this cause there was a cancer registration, but these did not help identify the site of the primary cancer in most cases, since for 28 the registration was also of an ill-defined or secondary cancer.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This finding is consistent with radiation being a cause of these cancers, but does not account for most of the excess being among those not monitored for radiation exposure. An excess of these cancers has not been found in other studies of nuclear workers and nor has an association with radiation dose (Beral et al, 1988;Fraser et al, 1993), and our findings are difficult to interpret. For 35 of the 53 deaths from this cause there was a cancer registration, but these did not help identify the site of the primary cancer in most cases, since for 28 the registration was also of an ill-defined or secondary cancer.…”
Section: Discussioncontrasting
confidence: 96%
“…The findings of mortality are very similar to those reported in our earlier paper (Smith & Douglas, 1986). In other studies of workers in nuclear plants, overall mortality rates have been found to be substantially lower than those of the general population (Beral et al, 1988;Wing et al, 1991;Fraser et al, 1993;Gilbert et al, 1993) and this has usually been attributed to the 'healthy worker' effect, often found in studies of occupational mortality, resulting from higher death rates in the general population among individuals with chronic sicknesses who either do not seek employment or who are not selected for employment. We commented at some length on the apparent absence of this effect among the Sellafield workers (Smith & Douglas, 1986) and concluded that it seemed unlikely that such an effect was masked owing to a deleterious effect of radiation exposure, the two principal reasons being that overall mortality rates were lower among radiation workers than among other workers and that there was little evidence of an association between accumulated radiation dose and death rates from all causes combined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These databases are of a generally high quality, not only because radiation dose records have to be maintained for United Kingdom regulatory purposes, but also because the data have been used previously for several large epidemiological studies of the workers themselves. [15][16][17][18][19][20][21][22] Data were supplied for all those responding who had ever had, or who had ever attempted to have, children, and were linked by computer to the cleaned, coded, and validated questionnaire based data with the subjects' unique personal identifiers. Thus the researchers were blind to the occupational exposure status of the workers when collecting data on reproduction and child health outcomes.…”
Section: Study Populationmentioning
confidence: 99%
“…1-4 6 8 10 14 Generally, when an occupational hazard is suspected the health of the workers in the industries concerned is studied directly: for example, within the nuclear industry, several cohort studies have investigated the relation between cancer and mortality in relation to exposure to ionising radiation at work. [15][16][17][18][19][20][21][22] The nuclear industry family study takes this one step further, linking the occupational exposure of workers to their pregnancies and the health of their children.…”
mentioning
confidence: 99%